Product and process design principles : synthesis, analysis, and evaluation - Seider, Warren D.; Seider, Warren D. (Hoboken, NJ : Wiley, 2009)
Armed with this book, chemical engineers will have a collection of modern strategies for the design of chemical products and processes. It emphasizes a systematic approach and integrates product design more thoroughly throughout the chapters. New case studies on process design are included to make the concepts more relevant.
1. Introduction to Chemical Product Design 1S Supplement to Chapter 1 2. Product-Development Process PART 1 BASIC CHEMICALS PRODUCT DESIGN 3. Materials Technology for Basic Chemicals: Molecular-Structure Design 3S Supplement to Chapter 3 4. Process Creation for Basic Chemicals 5. Simulation to Assist in Process Creation 6. Heuristics for Process Synthesis 7. Reactor Design and Synthesis of Networks Containing Reactors 7S Supplement to Chapter 7 8. Synthesis of Separation Trains 9. Heat and Power Integration 9S Suppliment to Chapter 9 Second Law Analysis 10. Mass Integration 11. Optimal Design and Scheduling of Batch Processes 12. Plantwide Controllability Assessment 12S Supplement to Chapter 12 Flowsheet Controllability Analysis 13. Basic Chemicals Product Design Case Studies PART 2 INDUSTRIAL CHEMICALS PRODUCT DESIGN 14. Materials and Process/Manufacturing Technologies for Industrial Chemical Products 15. Industrial Chemicals Product Design Case Studies PART 3 CONFIGURED CONSUMER PRODUCT DESIGN 16. Materials, Process/Manufacturing, and Product Technologies for Con"?gured Consumer Products 16S Supplement to Chapter 16 17. Con"?gured Consumer Product Design Case Studies PART 4 DETAILED DESIGN, EQUIPMENT SIZING, OPTIMIZATION, AND PRODUCT-QUALITY ANALYSIS 18. Heat Exchanger Design 19. Separation Tower Design 20. Pumps, Compressors, and Expanders 21. Polymer Compounding 22. Cost Accounting and Capital Cost Estimation 22S Supplement to Chapter 22 23. Annual Costs, Earnings, and Pro"?tability Analysis 23S Supplement to Chapter 23 24. Design Optimization 25. Six-Sigma Design Strategies PART 5 DESIGN REPORT 26. Written Reports and Oral Presentations APPENDIXES INDICES
Rev. ed. of: Product and process design principles / Warren D. Seider, J.D. Seader, Daniel R. Lewin. c2004. 2nd ed.
Includes bibliographical references and indexes.
Keywords: Chemical processes